Tipe dan Fungsi Humor dalam Acara Indonesia Lawak Klub di Trans 7 - Ema Suaib; Zainal Rafli; Liliana Muliastuti (Balai Bahasa Provinsi Riau, 2019)
The humor type and function contained in the Indonesian Lawak Klub (ILK) program are interesting to research. There are three types of humor theories in ILK that explain the reasons why someone can laugh or smile. The three types of humor are the theory of liberation (release), the theory of excellence (superiority), and the theory of incongruity. Whereas the seven functions of humor as communication activities in the social context discussed in this paper are the functions of social control, face-searching tools, building common ground, intelligence, regulating discourse, strengthening social bonds of friendship, and improving tense situations. This research aims to describe the type of humor theory and the function of humor contained in the ILK program. This research uses the method of qualitative description with observing, note-taking, and study literature techniques. The results of this research then find out how things can arouse laughter or amusement on someone and various functions of humor that are spoken by speakers. This research also illustrates that utterances or dialogues in ILK containing implicatures can produce broader speech meanings than just ordinary utterances. With implicature and humorous discourse in dialogue, criticism and control of the government, the most dominant type of humor theory that appears in ILK is the type of peculiar theory. Whereas the most dominant function of humor appears in ILK is functioned as a tool to improve tense and rigid situations.